The role of therapeutic optimism in recruitment to a clinical trial in a peripartum setting: balancing hope and uncertainty - Hallowell, N; Snowdon, C; Morrow, S; Norman, J; Denison, F; Lawton, J (BioMed Central, 2016)
Background: Hope has therapeutic value because it enables people to cope with uncertainty about their future health. Indeed, hope, or therapeutic optimism (TO), is seen as an essential aspect of the provision and experience of medical care. The role of TO in clinical research has been briefly discussed, but the concept, and whether it can be transferred from care to research and from patients to clinicians, has not been fully investigated. The role played by TO in research emerged during interviews with staff involved in a peripartum trial. This paper unpacks the concept of TO in this setting and considers the role it may play in the wider delivery of clinical trials. Methods: The Got-it trial is a UK-based, randomised placebo-controlled trial that investigates the use of sub-lingual glyceryl trinitrate (GTN) spray to treat retained placenta. Qualitative data were collected in open-ended interviews with obstetricians, research and clinical midwives (n =27) involved in trial recruitment. Data were analysed using the method of constant comparison. Results: TO influenced staff engagement with Got-it at different points in the trial and in different ways. Prior knowledge of, and familiarity with, GTN meant that from the outset staff perceived the trial as low risk. TO facilitated staff involvement in the trial; staff who already understood GTN’s effects were optimistic that it would work, and staff collaborated because they hoped that the trial would address what they identified as an important clinical need. TO could fluctuate over the course of the trial, and was sustained or undermined by unofficial observation of clinical outcomes and speculations about treatment allocation. Thus, TO appeared to be influenced by key situational factors – prior knowledge and experience, clinical need and observed participant outcomes. Conclusions: Situational TO plays a role in facilitating staff engagement with clinical research. TO may impact on trial recruitment by enabling staff to sustain the levels of uncertainty, or individual equipoise, necessary to collaborate with research while also responding to patients’ clinical needs. Staff may benefit from training to deal with fluctuations in TO.